Let's fill in the blanks step by step for the given problem.
-
y-terms: \[ 3/7y - y/7 \] To combine these terms: \[ 3/7y - y/7 = y(3/7 - 1/7) \] Here, \(1/7\) comes from \(-y/7\). So: \[ 3/7 - 1/7 = 2/7 \] Thus, you have: \[ 2/7y \]
-
x-terms: \[ -x/4 + 13x/4 \] To combine these terms: \[ x(-1/4 + 13/4) = x(12/4) = 3x \]
-
Constants: \[ 10 - 23 \] This simplifies to: \[ 10 - 23 = -13 \]
Now, putting everything together, the combined expression from the three parts is:
\[ \frac{2}{7}y + 3x - 13 \]
So the completed version is:
- y-terms: \( - y/7 \) and \( 2/7 \)
- x-terms: \( 13/4 \)
- Constants: \( 10 \)
The final answer to the addition of the expressions is:
\[ \frac{2}{7}y + 3x - 13 \]